Biomass energy consumption and carbon neutrality in OECD countries: Testing pollution haven hypothesis and environmental Kuznets curve - Wang, Yujing; Guan, Weimin; Liu, Ling; Ma, Xinyuan (Frontiers in Environmental Science, 2022)
The rising pollution enhances the need for eco-friendly measures such as technological development and the enhancement of nonrenewable energy resources to achieve sustainable economic progress. Biomass energy consumption is an innovative form of renewable energy source which influence the environment positively. The current study explores the impact of biomass energy consumption and Foreign Direct Investment on the environmental degradation of 32 OECD countries under the framework of the Environmental Kuznets Curve (EKC) hypothesis from 1990 to 2018. The Cross-Sectional ARDL estimation method has been deployed to address slope heterogeneity and cross-section dependency. The long-run result shows that biomass energy consumption reduces environmental pollution, while Foreign Direct Investment exerts pressure on the environmental quality, endorsing the pollution heaven hypothesis. Moreover, the findings validate the EKC hypothesis in the long run. The error correction term is significantly negative, confirming the convergence towards long-run equilibrium with a 46% adjustment rate. The robustness of the estimated model is also verified using alternative estimators. The study's outcome is encouraging the policymakers to devise policies for using biomass energy sources as alternative clean energy to ensure a sustainable environment.